Creativity: The impact of psychological capital and curiosity from the employee’s perspective in Bandung, Indonesia - Manik, Ester; Sidharta, Iwan; Zulfikar, Vicky Achmad; Rahman, Robbi Saepul; Fitria, Bulan Tati; Resawati, Retno; Nurdiansyah, Haris (International Journal of Management and Sustainability, 2023)
Creativity is a determining factor of organizational success. To engage employees with a high level of creativity, it is necessary to encourage excellent psychological capital and employee curiosity. This study examines the effect of psychological capital on employee creativity, mediated by curiosity. Research on creativity is closely related to curiosity as well as psychological capital; however, there is still a research gap. Therefore, our research focuses on the relationship between these variables. It employed a survey to gather data from 222 employees in seven retail store branches in Bandung, Indonesia. To evaluate the hypothesis proposed by the authors, partial least squares structural equation modeling (PLS-SEM) was used. The results indicated that psychological capital had an effect on employee creativity that was mediated by curiosity. The study results suggest that organizations can empower employees by increasing psychological capital and employee curiosity.